Cardiorespiratory motion‐tracking via self‐refocused rosette navigators. Issue 5 (7th January 2019) - Rigie, David; Vahle, Thomas; Zhao, Tiejun; Czekella, Björn; Frohwein, Lynn J.; Schäfers, Klaus; Boada, Fernando E.
Abstract : Purpose: To develop a flexible method for tracking respiratory and cardiac motions throughout MR and PET‐MR body examinations that requires no additional hardware and minimal sequence modification. Methods: The incorporation of a contrast‐neutral rosette navigator module following the RF excitation allows for robust cardiorespiratory motion tracking with minimal impact on the host sequence. Spatial encoding gradients are applied to the FID signal and the desired motion signals are extracted with a blind source separation technique. This approach is validated with an anthropomorphic, PET‐MR‐compatible motion phantom as well as in 13 human subjects. Results: Both respiratory and cardiac motions were reliably extracted from the proposed rosette navigator in phantom and patient studies. In the phantom study, the MR‐derived motion signals were additionally validated against the ground truth measurement of diaphragm displacement and left ventricle model triggering pulse. Conclusion: The proposed method yields accurate respiratory and cardiac motion‐state tracking, requiring only a short (1.76 ms) additional navigator module, which is self‐refocusing and imposes minimal constraints on sequence design.